Penetration capability of three different light curing units to composite-resin as measured by radiometer - Hartman, Henri (Universitas Padjadjaran, 2018)
Introduction: Composite-resin is widely used as a restorative material in dental practice on a daily basis when it comes to an aesthetic consideration. The purpose of this study is to investigate and compare the light penetration capabilities of three light curing units (LCU) through layers of composite resin using a radiometer. Method: Composites resin discs (2mm thick with 8 mm diameter) were cured out of seven different shades. Each specimen were used as a barrier, and a light source from three different LCUS was then applied through it. The radiometer was used to record the intensities of each LCU. Result: LED.C (Woodpecker™) has the lowest penetration capabilities to pass through the barrier compared to all LCU. The output intensity (mW/cm2) of all LCU has decreased gradually. ANOVA test showed that there was the significant result (p<0.01) for each specimen. Conclusion: The differences composite-resin shade could decrease the penetration capability of LCU.